Requerimentos ambientais da espécie invasora Hydrilla verticillata em uma planície de inundação tropical. - Rodrigues, Roberta Becker (2008)
Hydrilla verticillata is a submersed freshwater macrophyte, considered a weed in several countries, where it dislocated indigenous species and compromised multiple uses of continental water bodies. Its presence was recently detected in the upper Paraná River floodplain, where large stands developed in the littoral zone of the main channel of this river. However, it is not found in lentic environments in this floodplain, where limnological characteristics are different from the Paraná River. Submersed macrophytes growth is limited by two main factors: nutrients and underwater light availability. The aim of this study was to assess, through microcosms experiments, H. verticillata growth responses to sediment nitrogen and phosphorus availability (sediment amendment and dose-response experiments), and its photosynthetic rates under different light intensities (light-photosynthesis experiment). Water, plants and sediment were sampled in H. verticillata stands close to Nupélia?s advanced research base in Porto Rico, Paraná, Brazil. Apical shoots were cultivated in different sediment nutrients concentrations for approximately 24 days, and growth rates were related to nutrients availability through variance analyses. Results from sediment amendment experiments indicate that H. verticillata growth in the floodplain is limited by nutrients availability. On the other hand, dose-response experiments did not show significant differences in growth rates with the different concentrations of sediment nutrients. Light-photosynthesis experiments where conducted inside sealed glass bottles, containing H. verticillata apical shoots and filtered water, submitted to different light intensities. Photosynthetic rates were determined in mg O2 g-1 DW h-1. H. verticillata showed effectiveness in light use, presenting low LCP and high k1/2. The results obtained here do not explain, alone, this species distribution in the floodplain, indicating that other factors must be acting in its distribution in this Environmental Protection Area.